PENGETAHUAN MAKANAN JAJANAN DENGAN METODE PENDIDIKAN KESEHATAN DAN VIDEO ANIMASI PADA ANAK SEKOLAH - Ardianty, Septi (IKesT Muhammadiyah Palembang, 2025)
Background: School age children according to the World Health Organization (WHO) are children aged 7-15 years. Children at school usually have problems choosing food, children tend to prefer food that is outside the home. Because of children's penchant for overeating, snacks are often found in everyday life. As the proportion of children who consume snacks increases, this will have an impact on health. Objective: to provide health education on choosing healthy snacks. For school-aged children, it is hoped that students will be able to choose snacks that are safe and healthy to consume so that problems do not occur. on his health. Method: in the form of showing animated videos, explaining the material in lectures and evaluating educational participants. The population in this study were 7th grade students at SMP 3 Muhammadiyah Palembang with a total of 38 participants. Results: the ability to increase knowledge is good with the Wilcoxcon p-value test result of 0.001 (p-,0.05), so it can be interpreted that there is an influence of health education with animated videos on increasing knowledge in children at SMP 3 Muhammadiyah Palembang. Conclusion: Based on the implementation of health education activities with animated videos, it can increase the knowledge of students at SMP 3 Muhammadiyah Palembang, with videos and posters about snack foods it is hoped that it can minimize incidents of food poisoning that often occur in the school environment